Practices, perceptions and emotions of teachers in Argentina in times of the Covid-19 pandemic - Vergara, Gabriela; Fraire, Vanina; Manavella, Agustina; Salessi, Solana (IJERI: International Journal of Educational Research and Innovation, 2021)
The article presents an analysis of practices, perceptions and emotions around the corrections of teachers in Cordoba, Buenos Aires and Santa Fe (Argentina), who during the Preventive and Compulsory Social Isolation (ASPO) during 2020, carried out distance teaching due to health emergency. From a sociology of bodies and emotions, we describe the results of 387 cases, who responded to an online survey during June 2020, differentiating by educational levels and types of management. The secondary or middle level shows a greater workload, with favorable perceptions of what has been done, although with low levels of innovation. The place of affective aspects in the corrections is highlighted at the initial level. Teachers recognize that they are faced with a job that changes quantitatively and qualitatively, but that they comply with and believe they can adapt to technological changes, feeling mainly joy and pride in what they do. It is suggested to deepen the place of new skills in secondary school and the relationship between quantity and quality in the tests.